2007
DOI: 10.1615/critrevimmunol.v27.i3.30
|View full text |Cite
|
Sign up to set email alerts
|

PART I. Peptide ImmunotherapyNatural and Autoantibodies to Human T-Cell Receptor Vβ Segments: Potential Roles in Immunomodulation

Abstract: Although the manifestation of inflammatory autodestructive disease is the result of major immunological dysfunction, recent evidence indicates that the immune system attempts to compensate by the production of immunomodulatory autoantibodies. Healthy humans have low levels of naturally occurring autoantibodies directed against the first complementarity-determining region (CDR1) and third framework region (FR3) of their own T-cell receptor (TCR) Vbeta segments, but individuals suffering from rheumatoid arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…On the one hand, Adelman et al (2007) have reported that patients with rheumatoid arthritis and systemic lupus erythematosus have anti-TCR v beta autoantibodies that appear to limit the autoimmune reaction. The presence of complementary TCR in autoimmune patients with T1DM or other autoimmune diseases might similarly represent attempts by the immune system to control the autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, Adelman et al (2007) have reported that patients with rheumatoid arthritis and systemic lupus erythematosus have anti-TCR v beta autoantibodies that appear to limit the autoimmune reaction. The presence of complementary TCR in autoimmune patients with T1DM or other autoimmune diseases might similarly represent attempts by the immune system to control the autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a number of the TCR from diabetes not only recognize insulin but also mimic it, suggests that some of the anti-insulin antibodies found in T1DM may also recognize such TCR as antigenic targets. Such TCR-targeted autoantibodies might, as Adelman et al (2007) suggest, serve to down-regulate the autoimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding what triggers this set of complementary interactions, and how the set can be regulated, may provide new and important insights into the prevention and control of diabetes. Given Marchelonis's observation of antibody-TCR binding in other autoimmune diseases [53], it is likely that autoimmune diseases in general will turn out to display the antigen mimicry complicated by idiotype-antiidiotype network of TCR-BCR-antibody interactions that we have characterized here.…”
Section: Discussionmentioning
confidence: 89%
“…From this perspective, anti-TCR antibodies might also represent a regulatory mechanism invoked by the immune system to dampen the autoimmune response. Thus, Marchelonis [53] has reported that patients with rheumatoid arthritis and systemic lupus erythematosus have anti-TCR V beta autoantibodies that may limit the autoimmune reaction. The presence of complementary TCR in autoimmune patients with T1DM or other autoimmune diseases might similarly represent attempts by the immune system to control the autoimmune process.…”
Section: Mmt Ait Act and Complementary Immune Responses: Causes Or mentioning
confidence: 99%
“…Such surface molecules include adhesion molecules and other receptors, which are likely involved in cell-cell interaction or outside-in signaling into lymphocytes and antigen-presenting or inflammatory cells [4,[16][17][18][19][20]. responses, since this cytokine is key to development and maintenance of T regulatory cells and is involved also in the expansion and activation of effector T cells and natural killer cells during immune responses [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%